PENGARUH DISIPLIN KERJA, INTERNAL LOCUS OF CONTROL, DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI NON-PNS PADA UPTD PJI KALIGENDING - Wiwit Panggihraharjo; Dani Rizana (JianE (Jurnal Ilmu Administrasi Negara), 2026)
This study aims to analyze the effect of work discipline, internal locus of control, and motivation on the performance of non-civil servant employees at UPTD PJI Kaligending, Kebumen Regency. This research employed a quantitative approach using a survey method involving 35 respondents. Data were analyzed using multiple linear regression, with hypothesis testing conducted through t-tests, F-tests, and the coefficient of determination (R²). The results indicate that partially, work discipline, internal locus of control, and motivation have a positive and significant effect on performance. Simultaneously, the three independent variables also significantly influence employee performance. The coefficient of determination shows that 68.4% of the variance in performance can be explained by the independent variables included in the model, while the remaining 31.6% is influenced by other factors not examined in this study. These findings highlight the importance of strengthening behavioral, psychological, and motivational aspects in improving employee performance.